Interpretation of “Ngahiang” Prabu Siliwangi in Babad Tanah Sunda Cirebon - Adiwinata, Syan Rosyid; Nabilah, Siti (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
The  purpose  of  this  study  is  to  scientifically  reveal  the  meaning  of  Prabu  Siliwangi's  “Ngahiang”  which  appears  in  the  Babad  Tanah  Sunda  Babad  Cirebon.  Not  only  in  the  Babad,  but  this  is  in  several  history  books  (Historiography)  especially  those  that  review  the  fall  of  the  Pajajaran  Kingdom.  This  research  focuses  on  finding  the  truth  of  the  meaning  of  Prabu  Siliwangi's  “Ngahiang”  and  also  so  that  it  can  be  rationally  accepted  about  several  possibilities  of  Prabu  Siliwangi's  existence  at  that  time  the  Pajajaran  Kingdom  was  being  visited  by  the  Cirebon  Sultanate.  This  research  method  uses  literature  studies  from  relevant  historiography  as  well  as  from  journal  articles  and  news  that  review  Prabu  Siliwangi  as  well  as  archaeologically  valid  historical  sites. Researchers  use  the  philological  method  approach  as  the  main  source  and  also  anthropology. Data  analysis  also  uses  Descriptive  Qualitative  so  that  this  article  can  describe  phenomena  or  events  that  are  currently  taking  place.  The  result  of  this  research  is  that  the  meaning  of  the  word  “Ngahiang”  of  Prabu  Siliwangi  is  not  moksa  or  disappearing  without  a  trace  from  the  face  of  this  earth  but  there  are  natural  causes,  including  illness  due  to  old  age.